Grebeg Penjalin: Komoditifikasi Budaya pada Pemberdayaan Masyarakat Desa Wisata Rotan Trangsan-Sukoharjo - Sarjiyanto Sarjiyanto; Ana Shohibul; Sarwoto Sarwoto; Mulyadi Mulyadi; Suryadari Istiqomah (Universitas Muhammadiyah Surabaya, 2022)
The purpose of community service in the Trangsan Rattan Tourism Village is to maintain the sustainability of the existence of the rattan industry center. This activity also aims to empower the potentials that are in the location and synergize the socio-economic and cultural potential in an effort to increase empowerment and improve the welfare of citizens in Rotan Tourism Village. The dedication method uses a study-action and participatory approach. Culture as an agent of change through the creation of the cultural event